Current Understanding of the Transmission, Diagnosis, and Treatment of H. pylori Infection: A Comprehensive Review - Aljaberi, Hend Sadeq Mohammed; Ansari, Nida Khalid; Xiong, Mengqiu; Peng, Hongxin; He, Bangshun; Wang, Shukui (International Journal of Medical, Pharmacy and Drug Research, 2023)
H. pylori infection is a prevalent bacterial infection that affects the gastric mucosa of humans, with a prevalence ranging from 30% to 90%, depending on the region. The infection is a significant cause of gastritis, peptic ulcer disease, and gastric cancer. In this comprehensive review, we discuss the current understanding of the transmission, diagnosis, and treatment of H. pylori infection. We describe the risk factors and epidemiology of the infection, along with its pathogenesis, which involves multiple virulence factors that contribute to the colonization and survival of the bacteria in the acidic stomach environment. Diagnostic tests for H. pylori infection include invasive and non-invasive methods, with the choice of test depending on several factors. Treatment of H. pylori infection is aimed at eradicating the bacteria and preventing complications. Antibiotic-based triple or quadruple therapy, in combination with acid-suppressing agents, is the standard treatment, but antibiotic resistance is an emerging problem that needs to be addressed. This comprehensive review provides a useful resource for clinicians, researchers, and public health officials involved in managing H. pylori infection and its associated complications.